Phytoremediation Ability of Ornamental Plants Celosia argantea L. and Mirabilis jalappa L. in Plumbum (Pb) Contaminated Soil - Juhriah Juhriah; Dian Islamiah; Muhammad Ruslan Umar (Fakultas MIPA UNM, 2023)
Plumbum or lead is a type of heavy metal that is dangerous if it has exceeded the threshold of 0.07 µg/g based on the National Standardization Agency SNI 2004. This type of heavy metal is found in nature such as in soil, water, and air. The purpose of the study was to determine the phytoremediation ability of two types of ornamental plants, namely Celosia argentea L. and Mirabilis jalappa L., against Plumbum (Pb) metal in soil. The growth parameters observed consisted of plant height, plant stem diameter, number of leaves, leaf length, and leaf width. The ICP-MS (Inductively coupled plasma-mass spectrometry) was used to analyze the plumbum (Pb) content in soil and plants. The results ofinitial soil analysis prior to the plant planting process (phytoremediation) were 103.17 µg/g which had exceeded the predetermined threshold. The result of the analysis after phytoremediation of Celosia argentea L. showed plumbum (Pb) content of 49.685 µg/g in soil and 1,9548 µg/g in plants. Similarly, the analysis of Ph content after phytoremediation of Mirabilis jalappa L. was 47.802 µg/g in soil and 5.3077 µg/g in plants. Based on biomass calculation of Celosia argentea L. and Mirabilis jalappa L., the obtained Plumbum (Pb) content was 18.84% and 27.85%, respectively. The percentage of Pb removal of Celosia argentea L. was 51.842%, while Mirabilis jalappa L. was 53.667%. The efficiency of Pb absorption of Celosia argentea L. and Mirabilis jalappa L. was 1.895% and 5.145%, respectively. In conclusion, Ornamental plants Celosia argentea L., and Mirabilis jalappa L., are able to act as phytoremediation agents for Plumbum (Pb) metal that pollutes the soil as evidenced by the decrease in Pb levels in the soil after the phytoremediation process.Keywords: Plumbum (Pb), Phytoremediation, Celosia argentea L., Mirabilis jalappa L.